Pesan Dakwah Dalam Konten Tiktok Ustadz Syamsudin Nur Ahmad Pada Akun @Syamtheceo - Wulandari, Rindyani Putri; Narulloh, Lalu (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
Currently the media is shifting to the era of new media (new media), one form of new media is social media. Social media has many platforms such as Instagram, Facebook and the one that currently has the most users is the social media tiktok. At the beginning of its appearance, TikTok was blocked by the Ministry of Communication and Information in 2018, but since the block was opened by the Ministry of Communication and Information with the terms and conditions that apply, TikTok has become the most downloaded social media application. Tiktok is currently also used as a means of creativity and a medium for conveying messages and also preaching. Related to this, the problem of this research is how da'wah messages are conveyed on social media tiktok. As for this study, the researcher chose Ustadz Syamsudin Nur Ahmad's tiktok account, namely @SyamTheCEO as the research object. This study uses a descriptive qualitative research method with a textual analysis approach that aims to explore, interpret, and at the same time deconstruct the ideology, values, or interests that are behind a media text in the da'wah messages contained in the tiktok content of Ustadz Syamsudin Nur Ahmad on his tiktok account based on the logic of textual analysis (denotation, connotation, myth). The results of this study explain the contents of the message of the propagation of aqidah, namely faith in Allah and faith in Qada and Qadar, namely believing in and having faith in Allah and believing in the decrees of Allah SWT's destiny. The contents of the moral da'wah message explained are morals to Allah and morals to humans. The contents of the preaching of worship messages explained are about the laws relating to the pillars of Islam provisions, laws and conditions in carrying out worship in the month of Dzulhijjah and the virtues of worship in the month of Dzulhijjah.